EVALUATION OF TRIBOTECHNICAL PROPERTIES OF SELF-FLUSING COAT-ING BASED ON STRUCTURAL-ENERGY PARAMETERS - Бородій, Віктор; Мікосянчик, Оксана; Мнацаканов, Рудольф; Занько, Сергій; Малярчук, Ігор (Problems of Friction and Wear, 2022)
It was determined that one of the most promising approaches to predicting the wear resistance of friction pairs is the analysis of the wear rate of the friction unit by assessing the kinetics of changes in the structural and energy characteristics of the surface layers of materials. The paper presents a method for estimating the specific friction in tribotechnical contact for accelerated laboratory and bench tests in the study of structural materials, which can be used to predict the kinetics of changes in energy intensity of contact, the degree of activation of metal, the intensity of its deformation over time - the main indicators that affect the durability of the friction units of machines and mechanisms. It was determined that by selecting the optimal thickness of the nickel-based coating obtained by gas-flame spraying of self-fluxing granular powder PG-AN9 (ПГ-АН9), it is possible to obtain coatings characterized by high wear resistance in rolling with slippage conditions. The total linear wear of the leading and lagging surfaces in rolling with slippage conditions is 9.9 : 3.54 : 2.12 μm for coatings with a thickness of 0.3, 0.7 and 1.2 mm respectively. It was determined that increasing the thickness of the self-fluxing coating to 1.2 mm defines an increase in the microhardness of the surface layers, an increase in antifriction properties and a decrease in the intensity of wear. The self-fluxing coating exhibits a high load-bearing capacity in the contact load range of 150…450 MPa, which is due to the presence of nanostructured dispersed particles in the matrix. The coating under load does not undergo intense structural and energy transformations, as evidenced by the kinetics of changes in the specific work of friction during performance period: at the initial stage of performance, at a contact load of 150 MPa specific friction was 4800 J/mm2, during friction process, by increase of contact load up to 450 MPa, this parameter is reduced by 2.1 times. The main criterion of effective structural suitability of the coating is its high wear resistance, which is 2,2·1011 and 1,9·1011 for leading and lagging surfaces respectively.